Functional roles of multiple Ton complex genes in a Sphingobium degrader of lignin-derived aromatic compounds - Masaya Fujita (Nature Portfolio, 2021)
Abstract TonB-dependent transporters (TBDTs) mediate outer membrane transport of nutrients using the energy derived from proton motive force transmitted from the TonB–ExbB–ExbD complex localized in the inner membrane. Recently, we discovered ddvT encoding a TBDT responsible for the uptake of a 5,5-type lignin-derived dimer in Sphingobium sp. strain SYK-6. Furthermore, overexpression of ddvT in an SYK-6-derivative strain enhanced its uptake capacity, improving the rate of platform chemical production. Thus, understanding the uptake system of lignin-derived aromatics is fundamental for microbial conversion-based lignin valorization. Here we examined whether multiple tonB-, exbB-, and exbD-like genes in SYK-6 contribute to the outer membrane transport of lignin-derived aromatics. The disruption of tonB2–6 and exbB3 did not reduce the capacity of SYK-6 to convert or grow on lignin-derived aromatics. In contrast, the introduction of the tonB1–exbB1–exbD1–exbD2 operon genes into SYK-6, which could not be disrupted, promoted the conversion of β-O-4-, β-5-, β-1-, β-β-, and 5,5-type dimers and monomers, such as ferulate, vanillate, syringate, and protocatechuate. These results suggest that TonB-dependent uptake involving the tonB1 operon genes is responsible for the outer membrane transport of the above aromatics. Additionally, exbB2/tolQ and exbD3/tolR were suggested to constitute the Tol-Pal system that maintains the outer membrane integrity.